Bosworth Dislocation without Associated Fracture - Austin D. Williams; Matthew Blue; Christian Douthit; Cyrus Caroom (Case Reports in Orthopedics)
One of the rarest ankle injuries is the Bosworth fracture-dislocation, whereby the distal fibula fractures and is lodged behind the tibia and is often unable to be reduced in a closed fashion. Even more rarely, a Bosworth dislocation without any accompanying fractures may occur. In this case, a 19-year-old male presented with a Bosworth dislocation, with the ipsilateral tibia having previously undergone intramedullary nailing. After closed reduction was attempted, open reduction and fixation was performed, directly reducing the fibula and fixing the unstable syndesmosis with 2 quadricortical screws. Bosworth injuries are rare, yet severe, and should be treated in a timely manner. We were able to provide good reduction and fixation without requiring removal of the intramedullary nail, and we support the use of 2 quadricortical screws as a valid treatment option for the fixation of Bosworth dislocations.